Social media strategies to affect vaccine acceptance: a systematic literature review. (3rd August 2021) - Limaye, Rupali J.; Holroyd, Taylor A.; Blunt, Madeleine; Jamison, Alexandra F.; Sauer, Molly; Weeks, Rose; Wahl, Brian; Christenson, Kaitlin; Smith, Cathy; Minchin, Jamie; Gellin, Bruce
ABSTRACT: Introduction : Vaccine hesitancy, defined as a delay in the acceptance or the refusal of vaccines despite their availability, is a growing global threat. More individuals are turning to social media for health information, including vaccine information. As such, there is an opportunity to leverage online platforms as a means to disseminate and persuade individuals toward vaccine acceptance. We sought to review literature focused on the influence of exposure to social media content on vaccine acceptance or hesitancy. Areas covered : This review focused on social networking sites (e.g. Facebook) and content communities (e.g. YouTube), to understand how exposure to vaccine information affected vaccine knowledge, attitudes, and intentions/behaviors. We searched PubMed, CINAHL, Scopus, and Inspec. We included English-language materials published from 2004 to 2020 and included interventional studies, observational studies, and impacts of policies. We excluded systematic reviews, protocols, editorials, letters, case reports, case studies, commentaries, opinion pieces, narrative reviews, and clinical guidelines. Expert opinion : Social media interventions to affect vaccine acceptance is a new but growing area of study. How a communication message is framed, who delivers the message, and network structure are critical for affecting the vaccine decision-making process. Social media should be leveraged to impact vaccine uptake.